Effects of ocean acidification on fatty acid composition in the Antarctic snail Neobuccinum eatoni - Servetto, Natalia (2025)
Introduction: Ocean acidification (OA), resulting from the absorption ofincreasing atmospheric CO2 by the oceans, represents a major threat tomarine organisms. Despite growing concern, the biochemical responses ofAntarctic species to OA remain poorly understood.Methods: This study investigated the impact of OA (pH 7.70 ± 0.09) on the fattyacid (FA) composition of the Antarctic snail Neobuccinum eatoni over a twomonth experimental period (December 2015–March 2016). Fatty acid profileswere analyzed in multiple tissues to assess potential alterations induced by lowpH (LpH) conditions.Results: Significant tissue-specific changes in FA composition were detected,particularly in the mantle and gill. Under LpH exposure, notable modificationsoccurred in long-chain polyunsaturated fatty acids (LC-PUFAs) such as 22:5n-3,22:6n-3, and 24:5n-6. Elevated LC-PUFA levels in the mantle suggested acompensatory response to oxidative stress, while shifts in the n-3/n-6 ratios inthe gill pointed to potential alterations in immune and anti-inflammatory functions.Discussion: Indicators of homeoviscous adaptation (HVA), including PUFA/SFAratios and mean chain length (MCL), revealed biochemical strategies used by N.eatoni to maintain membrane fluidity under acidified conditions. This studyprovides the first evidence of FA-based responses to elevated pCO₂ in anAntarctic gastropod, highlighting the potential of fatty acids as sensitivebiomarkers of physiological adaptation to environmental stressors.